Spatiotemporal characteristics of extreme rainfall events over the Northwest Himalaya using satellite data. (15th January 2016) - Bharti, Vidhi; Singh, Charu; Ettema, Janneke; Turkington, T. A. R.
ABSTRACT: Using remotely sensed Tropical Rainfall Measuring Mission (TRMM) 3B42 version 7 precipitation data, an investigation on extreme rainfall events (EREs) during the monsoon season has been conducted over the Northwest Himalaya (NWH) for the period of 1998–2013. The satellite precipitation data have been validated with gridded rain gauge data prepared by India Meteorological Department (IMD) using standard statistical measures. A strong positive correlation of 0.88 is found between both, supporting the use of 3B42 V7 for the study of rainfall over the region. The EREs have been identified using three indices corresponding to 98th, 99th, and 99.99th percentiles of the rainfall distribution over the region. The 98th and 99th percentile thresholds are suggested to be considered as extreme and very extreme events respectively whereas 99.99th percentile may correspond to the cloudburst events. The parametric t ‐test results indicate a significant increasing trend of the frequency of EREs whereas non‐parametric Mann‐Kendall test results yield no significant trend of EREs over the study region. As the sample size is small, therefore the significance of these results may not be ascertained. The elevation exhibits strong inverse relation with frequency and intensity of EREs over the NWH. A strong negative correlation of ∼0.8 and a poor negative correlation of ∼0.48 are obtained between the elevation and frequency of extremes exceeding 98th and 99th percentiles, and frequency of the cloudburst events, respectively. Whereas, elevation shows strong negative correlations of −0.85, −0.84, and −0.81 with rainfall intensities associated with 98th, 99th, and 99.99th percentiles, respectively. The plains and foothills of the NWH region experience the highest frequency of EREs. However, the peaks of the highest frequency of events are also observed at different elevation ranges at state‐level analysis. This study is a contribution to the on‐going research of extreme events over the mountainous terrain including disaster management study.